CREATIVE ECONOMIC MANAGEMENT OF TANGKIT LAMA VILLAGE SUNGAI GELAM SUB-DISTRICT MUARA JAMBI DISTRICT - Sumarto Sumarto (State Institute of Islamic Studies (IAIN) Palu, 2018)
The potential of a dynamic society must be developed with good management of economic activities. Certainly by building a good standard of living with adequate income. This is done by the author conveying one of the potential of the Village in Muara Jambi Regency which could be the starting point of economic progress in Jambi. When viewed from the data, the village of Tangkit Lama is divided into 4 hamlets, namely Hamlet I, Hamlet II, Hamlet III, and Hamlet IV. The number of household in Tangkit Lama Village is 27. The number of householders in Tangkit Lama Village is 1094 households with a total population of 4046 people. The details of the male population are 2100 people and women are 1946 people. The village of Tangkit is rich in agricultural land, no wonder that most of the villagers work as farmers and farm laborers. The types of plants planted in this village include rubber, palm oil, corn, tobacco, chili, green beans and peanuts, kale, spinach, mustard greens, watermelons. The total area of agricultural land is 5730 ha, with details of 1500 ha residential area, 3879 ha of rubber plantation area, 200 ha of palm oil area, 20 ha of secondary crop area, and 121 ha of horticulture area. The people of Tangkit Lama village also have cattle and goats. The community can spend their free time after returning from the garden. This is usually done by men and women from the villages of Tangkit Lama. In the village of Tangkit Lama there are also many people who work as tailors who usually sew when there are clothes order or intentionally make clothes for sale. Various economic activities developed by the community, ranging from gardening, raising to sewing activities. This is very potential if developed can generate people’s economy through creative action, not only the potential that has been developed and has results, but needs sustainable development and hope can be a source of additional income for each household. Therefore, there is a need for good management in managing the economic activities of the community based on potential and development. In this paper the author tries to raise the reality of the village of Tangkit Lama in developing creative economic activities.